CLINICAL COURSE AND RISK FACTORS FOR THE DEVELOPMENT OF POLLINOSIS - Umurova N.M; Ismatova M.N (Scholar Express Journal, 2021)
Treatment and prevention of pollinosis is one of the most important and complex problems. Their relevance is characterized by a high frequency of occurrence of a close dependence on natural and climatic conditions. Currently, the importance of early diagnosis and treatment of allergic diseases is emphasized to promote active and healthy aging.
Keywords: Prevention of pollinosis; bronchial asthma; allergic condition; rhinocanyuktivitis